Drought and salinity stresses in barley: Consequences and mitigation strategies - EL SABAGH, Ayman; Hossain, Akbar; Islam, Md. Shohidul; Barutçular, Celaleddin; Hussain, Saddam; Hassannuzzaman, Mirza; Akram, Tauseef; Mubeen, Muhammad; Nasim, Wajid; Fahad,Shah; Kumar, Narendra; Meena,Ram Swaroop; et al. (Australian Journal of Crop Science, 2019)
Recent trends show reductions in crop productivity worldwide due to severe climatic change. Different abiotic stresses significantly affect the growth and development of plants, leading to decreased crop yields. Salinity and drought stresses are the most common abiotic stresses, especially in arid and semi-arid regions, and are major constraints for barley production. The present review attempts to provide comprehensive information related to barley plant responses and adaptations to drought and salinity stresses, including physiological and agronomic, in order to alleviate the adverse effect of stresses in barley. These stresses reduce assimilation rates, as they decrease stomatal conductance, disrupt photosynthetic pigments, reduce gas exchange, enhance production of reactive oxygen species, and lead to decreased plant growth and productivity. This review focuses on the strategies plants use to respond and adapt to drought and salinity stress. Plants utilize a range of physiological and biochemical mechanisms such as adaptation strategies, through which the adverse effects can be mitigated. These include soil management practices, crop establishment, as well as foliar application of anti-oxidants and growth regulators that maintain an appropriate level of water in the leaves to facilitate adjustment of osmotic and stomatal performance. The present review highlighted the adverse effect of drought and salinity stresses barley and their mitigation strategies for sustainable barley production under changing climate. They review also underscored that exogenous application of different antioxidants could play a significant role in the alleviation of salinity and drought stress in plant systems.